TRYING TO ACT An Empirical Study of Investigating Higher Education Consumers - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2002)
This article describes an investigation of consumer behavior. especicrilv teaming behavior, in a hi gher educat ion institution. Bago=i-Warshaw model (1990), also called the theory of trying, MIS used as the main reference in the research. Salient modal belielâ¢ have been developed. The model includes such variables as trying, intention to fry. frequency, recency, attitudes towards living, subjective, norms towards trying, attitudes towards success in tryins.